Regulating Lipase Inhibition by Adjusting Composition of Binary Mixtures of 1-Ethyl-3-Methyl Ethylsulfate and Propanol-1 - Ali, Md Ahad; Susan, Md Abu Bin Hasan (Dhaka University Journal of Science, 2026)
This study investigates the regulation of lipase inhibition in binary mixtures of 1-ethyl-3-methylimidazolium ethylsulfate ([C2mim]C2H5SO4) and propanol-1, focusing on their effects on catalytic activity and kinetics. The hydrolysis of p-nitrophenyl butyrate (p-NPB) was monitored spectroscopically to evaluate enzyme performance in aqueous, ionic liquid, and binary solvent systems. Results revealed that [C2mim]C2H5SO4 minimized lipase denaturation by reducing unfavorable interactions at the active site, while propanol-1 acted as an inhibitor by interfering with the serine active site and hydrophobic binding regions. Optimal enzymatic activity was observed at low propanol-1 content, whereas higher concentrations caused significant inhibition, slowing the reaction and hindering substrate accessibility. These findings highlight the delicate balance of ionic liquid–alcohol mixtures in tailoring enzyme activity and emphasize the importance of controlling solvent composition to optimize biocatalysis in non-aqueous media. Dhaka Univ. J. Sci. 74(1): 81-86, 2026 (January)